Multilevel analyses of related public health indicators: The European Surveillance of Congenital Anomalies (EUROCAT) Public Health Indicators. Issue 2 (26th February 2020) - Best, Kate E.; Rankin, Judith; Dolk, Helen; Loane, Maria; Haeusler, Martin; Nelen, Vera; Verellen‐Dumoulin, Christine; Garne, Ester; Sayers, Gerardine; Mullaney, Carmel; O'Mahony, Mary T.; Gatt, Miriam; et al.
Abstract: Background: Public health organisations use public health indicators to guide health policy. Joint analysis of multiple public health indicators can provide a more comprehensive understanding of what they are intended to evaluate. Objective: To analyse variaitons in the prevalence of congenital anomaly‐related perinatal mortality attributable to termination of pregnancy for foetal anomaly (TOPFA) and prenatal diagnosis of congenital anomaly prevalence. Methods: We included 55 363 cases of congenital anomalies notified to 18 EUROCAT registers in 10 countries during 2008‐12. Incidence rate ratios (IRR) representing the risk of congenital anomaly‐related perinatal mortality according to TOPFA and prenatal diagnosis prevalence were estimated using multilevel Poisson regression with country as a random effect. Between‐country variation in congenital anomaly‐related perinatal mortality was measured using random effects and compared between the null and adjusted models to estimate the percentage of variation in congenital anomaly‐related perinatal mortality accounted for by TOPFA and prenatal diagnosis. Results: The risk of congenital anomaly‐related perinatal mortality decreased as TOPFA and prenatal diagnosis prevalence increased (IRR 0.79, 95% confidence interval [CI] 0.72, 0.86; and IRR 0.88, 95% CI 0.79, 0.97). Modelling TOPFA and prenatal diagnosis together, the association between congenital anomaly‐related perinatal mortality and TOPFA prevalence became stronger (RR 0.70, 95% CI 0.61, 0.81). The prevalence of TOPFA and prenatal diagnosis accounted for 75.5% and 37.7% of the between‐country variation in perinatal mortality, respectively. Conclusion: We demonstrated an approach for analysing inter‐linked public health indicators. In this example, as TOPFA and prenatal diagnosis of congenital anomaly prevalence decreased, the risk of congenital anomaly‐related perinatal mortality increased. Much of the between‐country variation in congenital anomaly‐related perinatal mortality was accounted for by TOPFA, with a smaller proportion accounted for by prenatal diagnosis.